π-Excess σ2P,O Hybrid Ligands: Synthesis of the First 4-Methoxy-1H-1,3-benzazaphospholes - Aluri, Bhaskar R.; Jones, Peter G.; Dix, Ina; Heinicke, Joachim W. (Synthesis, 2014)
The synthesis of the first 4-methoxy-substituted 1,3-benzazaphosphole was accomplished by using a C,O-dilithium intermediate generated from N-(3-methoxyphenyl)-2,2-dimethylpropanamide and butyllithium. This intermediate was subjected either to direct phosphonylation or to a bromination and phosphonylation sequence; subsequent reductive cyclization with excess lithium aluminum hydride led to the desired product. In addition, N-(2,2-dimethylpropyl)-3-methoxy-2-phosphinoaniline, formed in a side reaction, was cyclized with (dimethoxymethyl)dimethylamine to give 1-(2,2-dimethylpropyl)-4-methoxy-1H-1,3-benzazaphosphole. The behavior of these +M-substituted π-excess aromatic σ2P-heterocycles towards moisture is reported, together with their 1H, 13C, and 31P solution NMR spectra and a crystal-structure analysis. The new compounds represent potential σ2P,O hybrid or chelate ligands with a high π-density at the phosphorus atom.
Keywords: lithiation; cross-coupling; phosphorus; ring closure; heterocycles; ligands